Estudo da composição química da semente da quinoa Chenopodium quinoa - Câmara, Arlene da (2020)
Chenopodium quinoa Wild, quinoa has been considered an important crop species because it has high biological value proteins and bioavailable essential amino acids, unsaturated lipids, dietary fibers, complex carbohydrates and other beneficial bioactive compounds, such as polyphenolic compounds. The objective of this work was to determine the chemical composition of the quinoa seed, kindly provided by the company Plantus LTDA, to quantify the main minerals present, to determine the most suitable condition for the extraction of the phenolic compounds, to quantify them and to evaluate the antioxidant activity. The analyzes of moisture, ash, lipids, crude fiber, proteins and carbohydrates were performed using the AOCS method. The determination of minerals used optical emission spectrometry with plasma (ICP / OES). The analysis of total phenolics was performed using the Folin - Ciocalteu method. The antioxidant activity was determined by the DPPH radical sequestration capacity according to the method proposed by Brand-Willians with modifications. The moisture content of the quinoa seed was 12.78 ± 0.031%, higher when compared to flaxseed, but the amount of ash (1.925% ± 0.014) was lower than the same seed. The lipid content was 11,07% ± 1.6 showing the richness of fatty acids in the seed. The crude fiber found was 7, 633% ± 1.0, with a value lower than that contained in flaxseed (35.5%) and that of sesame seed (11.9%) due to the method used. The protein value was 13,125% ± 1,4, presenting itself as the second most prevalent component, and due to this amount, the quinoa seed attracts the attention of researchers, mainly because it has a balance and efficiency similar to milk protein. The value of carbohydrates determined was approximately 53.34% ± 1.94, these being higher than the amount of carbohydrates present in flaxseed and sesame seeds. The analysis of minerals showed calcium and phosphorus as the predominant minerals with values of 100 and 31 mg.g-1, respectively. The concentration of phenolic compounds in the seed was 1.41 mg of gallic acid.g-1. The IC50 value determined by the DPPH method was 0.02 mg / g, showing the high antioxidant capacity of the seed. Thus, the results found in this work show that the quinoa seed has a high content of proteins, lipids and phenolic compounds and is relevant to the food area.